Unravelling the pharmacokinetics of aflatoxin B1: In vitro determination of Michaelis–Menten constants, intrinsic clearance and the metabolic contribution of CYP1A2 and CYP3A4 in pooled human liver microsomes - Lootens, Orphélie; De Boevre, Marthe; Gasthuys, Elke; Van Bocxlaer, Jan; Vermeulen, An; De Saeger, Sarah (Frontiers in Microbiology, 2022)
Mycotoxins, fungal secondary metabolites, are ubiquitously present in food commodities. Acute exposure to high levels or chronic exposure to low levels has an impact on the human body. The phase I metabolism in the human liver, performed by cytochrome P450 (CYP450) enzymes, accounts for more than 80 percent of the overall metabolism of exogenous and endogenous compounds. Mycotoxins are (partially) metabolized by CYP450 enzymes. In this study, in vitro research was performed on CYP450 probes and aflatoxin B1 (AFB1), a carcinogenic mycotoxin, to obtain pharmacokinetic data on AFB1. The CYP450 probes of choice were a CYP3A4 substrate, midazolam (MDZ) and a CYP1A2 substrate, phenacetin (PH) since these are the main metabolizing phase I enzymes of AFB1. Linearity experiments were performed on the three substrates indicating that linear conditions were achieved at a microsomal protein concentration and incubation time of 0.25 mg/mL and 5 minutes, 0.50 mg/mL and 20 minutes and 0.25 mg/mL and 5 minutes for MDZ, PH and AFB1, respectively. The Km was determined in human liver microsomes (HLM) and was estimated at 2.15 µM for MDZ, 40.0 µM for PH and 40.9 µM for AFB1. The associated Vmax values were 956 pmol/(mg.min)(MDZ), 856 pmol/(mg.min)(PH) and 11,536 pmol/(mg.min)(AFB1). Recombinant CYP systems were used to determine CYP450-specific Michaelis-Menten values for AFB1, leading to a CYP3A4 Km of 49.6 µM and an intersystem extrapolation factor (ISEF) corrected Vmax of 43.6 pmol/min/pmol P450 and a CYP1A2 Km of 58.2 µM and an ISEF corrected Vmax of 283 pmol/min/pmol P450. An activity adjustment factor (AAF) was calculated to account for differences between microsome batches and used as a correction factor in the determination of the human in vivo hepatic clearance for MDZ, PH and AFB1. The hepatic blood clearance corrected for the AAF CLH,B,MDZ,AAF, CLH,B,PH,AAF CLH,B,AFB1,AAF(CYP3A4) and CLH,B,AFB1,AAF(CYP1A2) were determined in HLM at 44.1 L/h, 21.7 L/h, 40.0 L/h and 38.5 L/h. Finally, inhibition assays in HLM showed that 45 % of the AFB1 metabolism was performed by CYP3A4/3A5 enzymes and 49 % by CYP1A2 enzymes. The remaining six percent might be metabolized by CYP2A13 enzymes, but further research is needed for confirmation.